Alternative realities : utopian thought in times of political rupture - Alternative Realities Conference; Lerner, Paul Frederick 1966- HerausgeberIn; Segal, Joes 1961- HerausgeberIn (Bulletin of the German Historical Institute Supplement, 2019)
A two-day conference organized by The Max Kade Institute for Austrian-German-Swiss Studies (USC) and The Wende Museum. Co-sponsored by the German Historical Institute and the Centre for Contemporary History, Potsdam (ZZF). Additional support provided by the Feuchtwanger Memorial Library, USC Dornsife Dean’s Office, and USC Dornsife Departments of Art History, History, and Slavic Languages and Literature. Modern history has been marked by periodic ruptures, radical changes brought on by wars, revolutionary upheaval, or sudden political shifts that shattered existing social and political structures and belief systems. No country has experienced this more profoundly than Germany, which has witnessed five regimes across the past 100 years and experienced both the heights of national euphoria and the depths of physical and moral defeat and destruction in the twentieth century. During times of fundamental change, cultural ideas and expressions pave the way for the imagination of a new order. This conference focuses on the key role of utopian visions, both artistic and intellectual, that changed the world from the twentieth century to the present day.